Gambaran Status Gizi Karyawan Pada PT Bina Sukses Lestari - Nina Isywara Kusuma; Muliana Muliana (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2023)
Introduction: Nutritional status is a balance between a worker's nutrient intake and better endurance. Nutritional status is one aspect of occupational health that has an important role in terms of work productivity. The nutritional intake of workers will be directly proportional to the nutritional status of the worker which can be translated through a normal Body Mass Index (BMI) in the range of 18.5 to 25. Work productivity is the ability of a person or group of people to produce goods or services. Increasing work productivity is required so that the employees can have more efficient, effective, and productive performance. Objective: The purpose of this study was to describe nutritional status in workers at the PT. Bina Sukses Lestari. Methods: This study uses observational (non experimental) method with semi quantitative approach. Data is obtained directly and virtually through interview methods and anthropometry measurements so that the types of data used are primary and secondary data. The instruments used are microtoise, weight scales. Result: The sample count consisted of 16 hotel employees with different positions and levels of physical activity. Based on the results of the calculation shows there are 5 people (31.25%) who have a skinny BMI and 11 people (68.75%) have a normal BMI. Conclusion: the BMI avarage of workers in normal status, with an avarage working time in 8 hours/day.